Difference of thrombocyte profile between obesity and central obesity in women - Hadisasmitajaya, Melki; Hendrianingtyas, Meita; Limijadi, Edward Kurnia Setiawan (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
Background: Obesity considered as a low-grade inflammation. Increased body fat has known to trigger inflammation. Platelet profile is a number of platelet-related parameters that can predict inflammation consisting of: platelet count (PLT), Platelet Larger Cell Ratio (P-LCR), Mean Platelet Volume (MPV). Differences in platelet profiles (PLT, P-LCR, MPV) in women with and without central obesity have only been investigated in a few studies.Objective: To prove differences in platelet profiles in women with and without central obesity.Materials and Methods: A cross-sectional observational study was conducted on 88 women with and without central obesity in RSND during July-September 2021. Data included age, abdominal circumference, hip circumference, PLT, P-LCR, and MPV. PLT, P-LCR, and MPV were measured using Sysmex XS-500i instrument. Statistical analysis was using Mann-Whitney test.Results: Mean of women PLT with and without central obesity were 338.72±71.09x103/uL and 309.09±44.36x103/uL. Difference platelet levels in women with and without central obesity was p=0.022. Median MPV of women with and without central obesity were 10.5 (8.5-11.8)fL and 9.7 (8.5-11.6)fL. Difference MPV values in women with and without central obesity was p=0.000. Median P-LCR of women with and without central obesity were 28.2 (12.3-44.3)% and 21.5 (15.2-37.1)%, respectively. Difference P-LCR value in women with and without central obesity was p=0.002.Conclusion: Platelet profiles (PLT, MPV, P-LCR) can be used as a marker of chronic low-grade inflammation in women with central obesity.Keywords : central obesity; MPV; PLT; P-LCR